Development Of A Stem E-Module Based On Project Based Learning On Chemical Equilibrium Material - Br Gurusinga, Dinda Natalisa; Eddiyanto, Eddiyanto; Lita Sirait, Agustina Ruth; Khairunisa, Dira; Ambarita, Graceana; Ayuandiva, Nabilla Sri; J. Sinaga, Zevi (Universitas Lampung, 2024)
This research aims to: (1) To determine the validity of the STEM e-module based on Project Based Learning (PjBL) on chemical equilibrium material. (2) To determine students' responses to STEM e-modules based on PjBL on chemical equilibrium material. The research background highlights the challenges of 21st century learning where learning is carried out by utilizing technology and using an independent curriculum where the learning process is student-centered. So the STEM-PjBL e-module is an alternative that students can use in the learning process with flexibility. Science, Technology, Engineering, and Mathematics (STEM) is an alternative learning solution for the 21st century. The development model used is the ADDIE Model which consists of five stages including Analysis, Design, Development, Implementation and Evaluation. The e-module assessment instrument is a validation instrument from material and design experts as well as a student response questionnaire in the form of a Likert scale. The research results show that (1) the validation of the STEM e-module based on PjBL on chemical equilibrium material is